Phylotranscriptomics and evolution of key genes for terpene biosynthesis in Pinaceae - Jiang, Kaibin; Du, Chengju; Huang, Linwang; Luo, Jiexian; Liu, Tianyi; Huang, Shaowei (Frontiers in Plant Science, 2023)
Pinaceae is the largest family of conifers, dominating forest ecosystems and serving as the backbone of northern, temperate and mountain forests. The terpenoid metabolism of conifers is responsive to pests, diseases, and environmental stress. Determining the phylogeny and evolution of terpene synthase genes in Pinaceae may shed light on early adaptive evolution. We used different inference methods and datasets to reconstruct the Pinaceae phylogeny based on our assembled transcriptomes. We identified the final species tree of Pinaceae by comparing and summarizing different phylogenetic trees. The genes encoding terpene synthase (TPS) and cytochrome P450 proteins in Pinaceae showed a trend of expansion compared with those in Cycas. Gene family analysis revealed that the number of TPS genes decreased while the number of P450 genes increased in loblolly pine. Expression profiles showed that TPSs and P450s were mainly expressed in leaf buds and needles, which may be the result of long-term evolution to protect these two vulnerable tissues. Our research provides insights into the phylogeny and evolution of terpene synthase genes in Pinaceae.